2021
DOI: 10.1519/jsc.0000000000003081
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Acceleration and High-Intensity Activities Between Small-Sided Games and Peak Periods of Official Matches in Elite Soccer Players

Abstract: Dalen, T, Sandmael, S, Stevens, TGA, Hjelde, GH, Kjøsnes, TN, and Wisløff, U. Differences in acceleration and high-intensity activities between small-sided games and peak periods of official matches in elite soccer players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Our data indicated that the differences between SSG NC and official matches were in line with previous studies, with players performing a greater number of accelerations and decelerations relative to time in SSG NC , but with higher peak speeds and VHSD covered during matches [9,12,14,36]. Unsurprisingly, this was due to the different relative areas per player available during SSG NC vs. official matches (81 m 2 vs. 300 m 2 ), as has been revealed in previous studies showing that a greater relative area per player results in more HSD and VHSD covered per player [10,12,13,31,33]. The comparison between SSG CA and official matches yielded a novel outcome of interest to practitioners and coaches, with greater running activity relative to time obtained during the SSG CA in comparison with the official matches, including HSD and VHSD travelled, in addition to a higher number of accelerations and decelerations.…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicated that the differences between SSG NC and official matches were in line with previous studies, with players performing a greater number of accelerations and decelerations relative to time in SSG NC , but with higher peak speeds and VHSD covered during matches [9,12,14,36]. Unsurprisingly, this was due to the different relative areas per player available during SSG NC vs. official matches (81 m 2 vs. 300 m 2 ), as has been revealed in previous studies showing that a greater relative area per player results in more HSD and VHSD covered per player [10,12,13,31,33]. The comparison between SSG CA and official matches yielded a novel outcome of interest to practitioners and coaches, with greater running activity relative to time obtained during the SSG CA in comparison with the official matches, including HSD and VHSD travelled, in addition to a higher number of accelerations and decelerations.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, unlike sprinting distance, the number of accelerations seems to be a considerable part of the training sessions. Indeed, recent findings indicate that small-sided games in training may have the same number of accelerations (>2 m·s −2 ) as peak periods of official matches [24]. Despite a difference in accelerations between starters and non-starters during training was confirmed, this difference had only a small effect.…”
Section: Discussionmentioning
confidence: 96%
“…This may be partially explained by the typology of drills used, where, usually, in the Portuguese training coaching philosophy, small-sided games are preferred. These games increase the frequency of accelerations/decelerations while decreasing opportunities to perform high-speed running or sprinting [19,20]. Therefore, the use of small-sided games may be part of an explanation to justify the increase of acceleration/deceleration load when compared to the match.…”
Section: Discussionmentioning
confidence: 99%